PENGARUH LINGKUNGAN KERJA DAN ETOS KERJA TERHADAP KINERJA GURU DIMEDIASI OLEH MOTIVASI KERJA DI SMP NEGERI 1 RAO - Ahmad Yusuf; Yesi Elsandra (Ensiklopedia of Journal, 2023)
This research is a quantitative research using a questionnaire technique using a Likert scale, with 46 teachers as respondents. With the aim of knowing the effect of the work environment and work ethic on teacher performance, mediated by work motivation at SMP Negeri 1 Rao. Data were analyzed using statistical methods with TCR descriptively and using the Partial Least Square (PLS) approach. The results of the study prove that partially the work environment and work motivation have a positive and significant effect on teacher performance. There is a significant positive influence between work ethic on teacher work motivation. The author suggests that the management of SMP Negeri 1 Rao always improves the quality of the existing work environment and work ethic, so as to maintain and increase teacher work motivation, so that teacher performance will be better in the future.Keywords: Work environment, work ethic, work motivation and teacher performance